1994
DOI: 10.1007/bf00305773
|View full text |Cite
|
Sign up to set email alerts
|

Rostro-caudal patterning of receptor-expressing olfactory neurones in the rat nasal cavity

Abstract: The rostro-caudal extent of odorant receptor expression zones in the rat olfactory epithelium was analysed by means of in situ hybridization. Three broad non-overlapping zones were identified that extended along almost the entire anterior-posterior axis; each zone was composed of several separate bands running anterior to posterior throughout the olfactory epithelium. Super-imposed onto these broad zones was the expression area of a particular receptor subtype (OR37); it was restricted to a small region of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(76 citation statements)
references
References 22 publications
5
71
0
Order By: Relevance
“…1 A). For the class II genes expressed in the OCAM-positive (non-zone 1) region, hybridization signals were confined to specific areas, as it has been reported previously (Ressler et al, 1993;Vassar et al, 1993;Strotmann et al, 1994) (Fig. 1 A).…”
Section: In Situ Hybridization Of Oe Sectionssupporting
confidence: 82%
See 1 more Smart Citation
“…1 A). For the class II genes expressed in the OCAM-positive (non-zone 1) region, hybridization signals were confined to specific areas, as it has been reported previously (Ressler et al, 1993;Vassar et al, 1993;Strotmann et al, 1994) (Fig. 1 A).…”
Section: In Situ Hybridization Of Oe Sectionssupporting
confidence: 82%
“…Each olfactory sensory neuron (OSN) expresses only one functional OR gene in a monoallelic manner (Chess et al, 1994;Malnic et al, 1999;Ishii et al, 2001;Serizawa et al, 2003), and expression of each OR gene is confined to a restricted area in the olfactory epithelium (OE) (Ressler et al, 1993;Vassar et al, 1993;Strotmann et al, 1994;Sullivan et al, 1996). Furthermore, OSNs expressing a given OR gene project their axons to a specific set of glomeruli in the olfactory bulb (OB) (Ressler et al, 1994;Vassar et al, 1994;Mombaerts et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…OSNs expressing a specific OR are scattered within four spatially distinct zones of the OE (Strotmann et al, 1992(Strotmann et al, , 1994Ressler et al, 1993;Vassar et al, 1993Vassar et al, , 1994Mombaerts et al, 1996;Sullivan et al, 1996;Tsuboi et al, 1999). Although initial studies suggested that these zones only partially overlap at their boundaries, recent results suggest that OR expression domains form a continuous gradient in the OE (Miyamichi et al, 2005).…”
Section: Expression Patterns Of Robo-2 and Slits In The Olfactory Systemmentioning
confidence: 99%
“…Olfactory sensory neurons (OSNs) that are located in the olfactory epithelium (OE) form highly stereotyped connections with second-order neurons within the olfactory bulb (OB). OSNs distributed within four spatially distinct zones of the OE project axons to four specific regions of the olfactory bulb (Strotmann et al, 1992(Strotmann et al, , 1994Ressler et al, 1993Ressler et al, , 1994Vassar et al, 1993Vassar et al, , 1994Mombaerts et al, 1996;Sullivan et al, 1996;Tsuboi et al, 1999). Although these zones are defined based on the segregated patterns of expression of odorant receptors in OSNs, there exists a certain degree of overlap in the expression patterns of olfactory receptors (ORs) within some of these zones (Norlin and Berghard, 2001;Iwema et al, 2004;Miyamichi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the chicken, catfish, and zebra fish, neurons expressing a particular OR gene appear to be randomly distributed throughout the entire olfactory epithelium (5,7,8,12). In contrast, studies performed with rodents have revealed that the OR genes are symmetrically distributed within the olfactory epithelium (13) throughout four broad zones, which consist of a series of elongated bands that extend along the anterior-posterior axis of the nasal cavity (2,14,15). Zonal segregation does not seem to be essential for coding a correct odor message since chicken and catfish, which efficiently detect odorants, show random distributions of OR genes within their olfactory epithelium.…”
mentioning
confidence: 99%